Pengaruh Terapi Psikoreligi terhadap Pengendalian Emosional pada Lansia di Kelurahan Legok Kota Jambi - vevi suryenti putri; Rahmi Dwi Yanti; Martha Suri (Jurnal Akademika Baiturrahim Jambi, 2023)
The increasingly heavy burden of life experienced by almost all people, can cause health problems both physically and psychologically. Psychoreligious therapy that is programmed properly can reduce the psychological burden so that it is effective for emotional control in the elderly. Psychoreligious therapy can be performed on the elderly by training the patient to carry out activities of prayer, remembrance, reading the Qur'an or other books and performing prayer activities. The research design used was a quasi-experimental design with one group pre-test and post-test design. Respondents in this study were all elderly people in RT 17, Legok Village, Jambi City, with a total sample of 20 respondents. Data collection was carried out using purposive sampling technique. Data analysis used the T test. The results showed that psycho-religious therapy had a significant effect on emotional control in the elderly with a p-value = 0.018 (p <0.05). The results showed that psychoreligious therapy had an effect on reducing emotional control scores in the elderly who experienced psychological stress. It is expected that the Putri Ayu Health Center in the field of mental nursing managers will plan to provide psychoreligious therapy to elderly patients on an ongoing basis and make a therapy schedule once every month.